ANALISIS JENIS USAHA DAN LABA ATAS BIAYA PADA PEDAGANG DI KABUPATEN MANOKWARI - Usman, Sarah (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2019)
The objective of this research is to analyze the potential of local traders' economic growth in Manokwari Regency, West Papua based on the type of product sold and the profit to cost ratio. This research uses a quantitative descriptive approach. The research sample consisted of 74 respondents taken randomly using a simple random sampling method at the traditional markets of Sanggeng Market and West Market. Data were processed using SPSS with descriptive statistical methods-frequency. Results showed that the most products sold in traditional markets in Manokwari Regency were tubers and fruits by 28.4%, followed by sea/livestock products and mixed products by 24.3%, and vegetables by 23%. The lowest profit to cost ratio was 0.9 and the highest was 60. The average profit to cost ratio was 7.52 which means that traders in Papua should have been at a better welfare level. Likewise, local businesses should have been grown better. Increasing local trader welfare is also increasing the level of local economic growth. However, many traders can only earn income to fulfill their daily needs. Therefore, they should improve their business skills and knowledge by following some business training and assistance programs.